2020
DOI: 10.3390/ijerph17093277
|View full text |Cite
|
Sign up to set email alerts
|

Biological Maturation and Hormonal Markers, Relationship to Neuromotor Performance in Female Children

Abstract: Background: Mechanisms that influence muscle strength can interfere with neuromotor performance and overall health, thus hormone markers and maturation can interact in this process. Objective: The present study aimed to verify the relationship of hormonal markers and biological maturation on neuromotor abilities in young people. Methods: This is a cross-sectional study with 44 female participants (11.5 ± 1.5 years). Hormones were analyzed biochemically. Skeletal and somatic maturation were analyzed using anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 45 publications
(72 reference statements)
0
26
2
Order By: Relevance
“…Each stage of puberty has different characteristics in relation to biological maturation; the endocrine system receives different stimuli, and hormonal levels stand out as one of the main differences between the different levels of puberty [11,12]. Subjects with precocious puberty generally have hormonal levels higher than those of late and synchronized puberty [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Each stage of puberty has different characteristics in relation to biological maturation; the endocrine system receives different stimuli, and hormonal levels stand out as one of the main differences between the different levels of puberty [11,12]. Subjects with precocious puberty generally have hormonal levels higher than those of late and synchronized puberty [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The maturation process resulting from adolescence is strongly governed by reactions from a range of hormones, which affect the maturation rhythm of young people in favor of the increase in sex hormones [15]. Sex hormones, such as estradiol, testosterone, and growth hormone, have extremely important functions in human biological development, which can mainly affect morphological structure, skeletal growth, and muscle strength levels [9][10][11][12][13][14][15][16][17]. In this context, among neuromuscular parameters, muscle strength and body speed are two of the most essential for body functionality in relation to physical health, and for the development of specific skills related to sports performance [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Azimi et al [4] identified that the muscular strength of young elite Iranian weight lifters was influenced by the accumulation of lean mass, however, the authors did not analyze the possible interaction of biological maturation, which could have confounded this interpretation. In addition, other studies have identified that BA, CA and sex all have independent significant relationships with the production of muscle strength in young athletes and non-athletes [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%